1987
DOI: 10.14198/mdtrra1987.9.04
|View full text |Cite
|
Sign up to set email alerts
|

Actividad del lagarto verdinegro (Lacerta schreiberi) (Sauria: Lacertidae)

Abstract: RESUMENEn este trabajo se estudia la actividad de Lacerta schreiberí en dos parcelas de Camposagrado (León). En arabas poblaciones se realizaron censos horarios de abril a septiembre. Para calcular el porcentaje de población activa en cada censo, se estimó simultáneamente y por separado para machos, hembras, subadultos y jóvenes el tamño de población en cada parcela.Los machos están más activos en primavera mientras que en verano apenas se ven. Las hembras presentan menor actividad que los machos y apenas se r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0
1

Year Published

1990
1990
2017
2017

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 4 publications
(6 reference statements)
0
4
0
1
Order By: Relevance
“…Previous studies indicate that activity body temperatures recorded in the field generally match preferred temperatures measured in the laboratory in diurnal lizards (Huey 1982). Field-active body temperatures are available for a subset of the species studied (Salvador and Arguello 1987;Van Damme et al 1987Brafia 1991;Castilla and Bauwens 1991;Gil 1992). Although these studies differ in methodology, scope, and study periods, they indicate that the distributions of field active body temperatures closely resemble those of the preferred temperatures, except in some high altitude and high latitude populations at the onset of the activity period (cf.…”
mentioning
confidence: 99%
“…Previous studies indicate that activity body temperatures recorded in the field generally match preferred temperatures measured in the laboratory in diurnal lizards (Huey 1982). Field-active body temperatures are available for a subset of the species studied (Salvador and Arguello 1987;Van Damme et al 1987Brafia 1991;Castilla and Bauwens 1991;Gil 1992). Although these studies differ in methodology, scope, and study periods, they indicate that the distributions of field active body temperatures closely resemble those of the preferred temperatures, except in some high altitude and high latitude populations at the onset of the activity period (cf.…”
mentioning
confidence: 99%
“…Body temperature (T b ) of lizards before hiding or immediately after emergence could not be measured with reliability given the experimental design. Field studies show that average T b of L. schreiberi is 31 • C, which is about 10 • C above air temperature (Salvador & Argüello, 1987). In a thermal gradient in the laboratory this lizard has a selected T b of 36.5 • C (Bauwens et al, 1995).…”
Section: Methodsmentioning
confidence: 93%
“…Our results indicated that the thermal environment at the point where the lizard was before the attack (T ext ), the thermal conditions inside the refuge (T int ) and the body mass of the lizard affected its refuge use decisions. On the one hand, lizards with presumably higher initial body temperatures (T b ) (i.e., higher T ext ; see Salvador & Argüello, 1987) and with a greater body mass (i.e., slower cooling rates) could hide for longer in the refuge. This is explained because these lizards could spend a longer time at low refuge temperatures before reaching a 'critical' low body temperature.…”
Section: Discussionmentioning
confidence: 99%
“…Efectivamente, los jóvenes de L. schreiberi basan su dieta en las tallas de presa mds abundantes, al igual que hacen los j6venes de L. vivipara (Heulin, 1986). En j6venes las demandas de energfa deben ser relativamente bajas (Stamps et al, 1981 ), dado que su actividad es muy escasa (Salvador, 1988 b). Para ellos parece ser mis rentable capturar las presas mAs abundantes.…”
Section: Categorias Taxon6micasunclassified